THE IMPLICATIONS OF THE CIRCULAR ECONOMY ON SUSTAINABLE ECONOMIC GROWTH - OCOLIȘANU Andreea; DOBROTĂ Gabriela; AGÂRBICEANU Marcela Simona (Management of Sustainable Development, 2022)
Although the regulatory framework and the conceptualization of the circular economy are still under development, a key role is assigned to the circular economy in the sense of saving resources, minimizing, and managing waste, reducing environmental degradation, while achieving beneficial economic and social results. This paper aims to highlight the impact of the circular economy on sustainable economic growth, by reviewing the specialized literature and impact studies. The transition to a global circular economy has gradually gained political attention, with the aim of promoting the circular economy by exploring synergies by working with other countries to achieve material circularity and, ultimately, decoupling resource use from macroeconomic growth. The result of the research reveals the existence of synergies between the circular economy and sustainable economic growth and the fact that the circular economy can lead to sustainable economic growth or well-being. These estimated positive effects at the global level cannot be generalized to the level of individual economies, due to the specificity of the sectors that support their economy and the degree of harmonization with the practices of the circular economy.